Correlation between Knowledge and Attitudes of Female Adolescents Towards Compliance with Iron Supplements - Nurhaera Nurhaera; Riana Pangestu Utami; Riska Mayang Saputri (Journal of Health and Nutrition Research, 2023)
The research aims to determine the correlation between the knowledge and attitudes of female adolescents toward compliance with consuming iron supplements at the Junior High School of SMPN 01 Long Bagun. This research was quantitative design research with a cross-sectional approach with a sampling technique using proportionate stratified random sampling. In selecting samples for each class, simple random sampling was used. The number of samples in this study was 79 female students at SMPN 01 Long Bagun, using questionnaires and interviews. Bivariate results show no significant relationship was found between knowledge and compliance with consuming iron supplements with a p-value of 0.2560 with r 0.129; also, no significant relationship between attitude and compliance with consuming iron supplements with a value of 0.0280.05 with r = 0.248. It is suggested that schools be able to carry out activities for drinking iron supplements together at school so that female adolescents can be controlled at predetermined and scheduled times and that the Community Health Center can provide counseling to young women on an ongoing basis and supervise schools regarding the implementation of drinking iron supplements together, as well as making efforts to carry out hemoglobin checks for them at school